Exploring social psychology / David G. Myers - Myers, David G. (McGraw-Hill series in social psychology, 2000)
Exploring Social Psychology provides a brief and economical introduction to social psychology, which presents concepts and findings in smaller bites - 30 modules that are crisp, concise, and ideally suited to students' attention spans. Written in the engaging Myers style the text attempts to reveal social psychology as an investigative reporter might, by providing a current summary of important social phenomena by showing how social psychology uncovers and explains such phenomena and by reflecting on their human significance. By focusing on humanly significant issues such as belief and illusion, independence and interdependence, love and hate, Myers presents social psychology in ways that inform and stimulate all students, not just future social psychologists. In addition, Module topics focus on the scope social psychology and on highlighting the scientific study of how we think about, influence, and relate to one another.